2012
DOI: 10.1074/mcp.m112.018135
|View full text |Cite
|
Sign up to set email alerts
|

A Cell Surfaceome Map for Immunophenotyping and Sorting Pluripotent Stem Cells

Abstract: Induction of a pluripotent state in somatic cells through nuclear reprogramming has ushered in a new era of regenerative medicine. Heterogeneity and varied differentiation potentials among induced pluripotent stem cell (iPSC) lines are, however, complicating factors that limit their usefulness for disease modeling, drug discovery, and patient therapies. Thus, there is an urgent need to develop nonmutagenic rapid throughput methods capable of distinguishing among putative iPSC lines of variable quality. To addr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 60 publications
(71 citation statements)
references
References 66 publications
2
69
0
Order By: Relevance
“…In comparison to the results of Van Hoof et al, 18 who examined the plasma membrane proteome of hESC-CM cultures and hF-CMs. The small overlap maybe attributed to the precipitation of plasma membrane proteins during 2D-differential-in-gel electrophoresis experiments and are, therefore, mostly excluded from our analysis 43 Gundry et al 44 examined published proteomic data on pluripotent stem cells and showed that overlap among different proteomic studies are generally small and this is consistent with what we observed. Of the ones that were found in both the studies, only 31% showed concordant changes between -handling proteins, 45 microRNAs, 46 and epigenetic components 47 that are determinants of the maturation of hESC-CMs.…”
Section: Discussionsupporting
confidence: 78%
“…In comparison to the results of Van Hoof et al, 18 who examined the plasma membrane proteome of hESC-CM cultures and hF-CMs. The small overlap maybe attributed to the precipitation of plasma membrane proteins during 2D-differential-in-gel electrophoresis experiments and are, therefore, mostly excluded from our analysis 43 Gundry et al 44 examined published proteomic data on pluripotent stem cells and showed that overlap among different proteomic studies are generally small and this is consistent with what we observed. Of the ones that were found in both the studies, only 31% showed concordant changes between -handling proteins, 45 microRNAs, 46 and epigenetic components 47 that are determinants of the maturation of hESC-CMs.…”
Section: Discussionsupporting
confidence: 78%
“…As the success of each of these applications will ultimately require the ability to efficiently and reproducibly select and track pluripotent cell derivatives at the appropriate developmental stage and subtype, new non-transgene based strategies for cell identification and selection will likely be required 55 . In this respect, proteomic technologies are predicted to a play major role in defining new cell surface markers to facilitate the identification and selection of cells [56][57][58][59][60] , similar to what is routine in the hematopoietic hierarchy [61][62][63][64] . However, proteomic technologies currently provide a snapshot averaged across the population of cells sampled.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies are based on the cell surface capture technology, which covalently labels extracellular glycan moieties on living cells (20). These studies focused for example on the surface proteome of stem cells (21), mesenchymal stromal cells (22), and murine adipocytes in obesity (23) as well as other immune cells such as B cell lines derived from lymphomas (24).…”
Section: Naive Cd4mentioning
confidence: 99%